The X-rays wind connection in PG 2112+059. Issue 1 (17th June 2021) - Saez, C; Brandt, W N; Bauer, F E; Chartas, G; Misawa, T; Hamann, F; Gallagher, S C
ABSTRACT: We study the connection between the X-ray and ultraviolet (UV) properties of the broad absorption line (BAL) wind in the highly X-ray variable quasar PG 2112+059 by comparing Chandra -ACIS data with contemporaneous UV HST /STIS spectra in three different epochs. We observe a correlation whereby an increase in the equivalent widths (EWs) of the BALs is accompanied by a redder UV spectrum. The growth in the BAL EWs is also accompanied by a significant dimming in soft X-ray emission (2 keV ), consistent with increased absorption. Variations in the hard X-ray emission (2 keV ) are only accompanied by minor spectral variations of the UV-BALs and do not show significant changes in the EW of BALs. These trends suggest a wind-shield scenario where the outflow inclination with respect to the line of sight is decreasing and/or the wind mass is increasing. These changes elevate the covering fraction and/or column densities of the BALs and are likely accompanied by a nearly contemporaneous increase in the column density of the shield.